2019
DOI: 10.1158/1078-0432.ccr-19-0836
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mitochondrial Inhibitor Blocks MAPK Pathway and Overcomes MAPK Inhibitor Resistance in Melanoma

Abstract: Purpose: The purpose of this study is to determine if inhibition of mitochondrial oxidative phosphorylation (OxPhos) is an effective strategy against MAPK pathway inhibitor (MAPKi)-resistant BRAF-mutant melanomas.Experimental Design: The antimelanoma activity of IACS-010759 (OPi), a novel OxPhos complex I inhibitor, was evaluated in vitro and in vivo. Mechanistic studies and predictors of response were evaluated using molecularly and metabolically stratified melanoma cell lines. 13 C-labeling and targeted meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 35 publications
5
54
0
Order By: Relevance
“…Our findings of BM hypoxia reduction by complex I inhibition with IACS-010759 clearly demonstrate the substantial metabolic origin of the BM intratumoral hypoxia. Resolution of measurable hypoxia upon arresting cellular respiration was likewise reported in multiple solid tumor models (38,42,43). The distinct oxidative metabolic requirements of leukemia (AML and recently CML) compared to normal hematopoietic stem cells (HSC) that predominantly utilize glycolysis for energy homeostasis, have been reported previously; and our work for the first time demonstrated a direct link to hypoxic responses.…”
Section: Discussionsupporting
confidence: 78%
“…Our findings of BM hypoxia reduction by complex I inhibition with IACS-010759 clearly demonstrate the substantial metabolic origin of the BM intratumoral hypoxia. Resolution of measurable hypoxia upon arresting cellular respiration was likewise reported in multiple solid tumor models (38,42,43). The distinct oxidative metabolic requirements of leukemia (AML and recently CML) compared to normal hematopoietic stem cells (HSC) that predominantly utilize glycolysis for energy homeostasis, have been reported previously; and our work for the first time demonstrated a direct link to hypoxic responses.…”
Section: Discussionsupporting
confidence: 78%
“…Several studies showed upregulation of OXPHOS in BRAF inhibitor-resistant melanoma cells, suggesting that targeting mitochondrial respiration could be an effective strategy to overcome MAPK inhibitor resistance [ 13 , 16 , 26 , 50 , 51 ]. In this context, we measured the activity of OXPHOS complexes in isolated mitochondria from vemurafenib-resistant RA375 cells compared to parental A375 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Therapy resistance is a major clinical challenge and the resistance of melanoma to targeted therapy is accompanied by some distinct changes in cellular metabolism, most notably upregulation of OXPHOS [ 13 , 16 , 26 , 50 , 51 ]. In this context, our analysis of enzymatic activities of OXPHOS complexes shows upregulation of complex IV in a BRAF inhibitor-resistant melanoma cell line.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations